2019
DOI: 10.3390/sym11030377
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Constitutive Model Analysis of High Parameter Steel Fiber Reinforced Concrete

Abstract: The traditional Holmquist-Johnson-Cook (HJC) constitutive model does not consider the effect of crack resistance, reinforcement and toughening effect of high parameter steel fiber on original concrete. The causes of the analysis effect of the high parameter reinforced concrete is not obvious. To address this problem, a dynamic constitutive model of high parameter steel fiber reinforced concrete is built in this paper. Based on the static constitutive model built by static force, a dynamic constitutive model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…Steel fiber is one of the most popularly used fibers to enhance the mechanical strength of concrete [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Nguyen et al indicated that the effects of rubber aggregates and fiber reinforcement could result in better cracking resistance for cement mortar [28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different mixing contents of PAN fibers added to RC have different effects on the freeze-thaw cycle damage of RC. For the purpose of investigating impact of PAN fiber mixing content on the frost durability of RC, the fiber factor k [43] was introduced to analyze the effect of PAN mixing content on the damage of RC, as shown in equation ( 8):…”
Section: Consequence Of the Mixing Content Of Pan Fibers On The Frost...mentioning
confidence: 99%
“…At present, domestic and foreign scholars have mostly constructed constitutive models that can characterize the dynamic damage evolution behavior characteristics of different types of concrete materials by modifying the existing dynamic damage constitutive models of concrete materials and have achieved certain research results 9–13 . For example, Luo 14 modified the strengthening and toughening effect of steel fiber and the strain rate effect on the basis of the original Holmquist–Johnson–Cook (HJC) model to obtain an improved constitutive model of high‐parameter steel fiber‐reinforced concrete that could effectively characterize the dynamic characteristics of steel fiber‐reinforced concrete and confirmed that the reconstruction simulation results were in good agreement with the test results. Dong et al 15 developed a dynamic impact constitutive model based on the modified viscoelasticity and damage theory that can better describe the stress–strain relationship of super‐fine stainless wire (SSW)‐reinforced reactive powder concrete at different strain rates, where the strain threshold is affected by both the strain rate and SSW volume fraction.…”
Section: Introductionmentioning
confidence: 99%